Diagnóstico do extrativismo e caracterização da qualidade de frutos de bacuri (Platonia insignis Mart.) em Santa Rita, Maranhão - Ericeira Júnior, José Carlos (2022)
Bacuri is a typical species of the Amazon region, with wide genetic variability among fruit trees with high potential, with possibilities of sustainable exploitation of fruit trees, such as the production of pulp, crystallized sweets, jams, juices, liqueurs, wines and others. delicacies, generating income and food, simultaneously. The bacuri has a high potential for exploitation and rich nutritional value, however, it is still very incipient, with rudimentary techniques, in an extractive way, as in the case of collection, not yet constituting a structured production chain. Today, the bacuri chain is characterized solely by extractivism. The bacuri is found in a niche of plants that originate rich products, extracted from the Amazon rainforest and has enormous productive potential, and can be consumed in several ways. Thus, the objective of this work was to characterize the quality of bacuri fruits associated with collection extractivism in two villages located in the municipality of Santa Rita, MA. The analyzes were carried out at the UEMA laboratory, where fruit mass, peel mass, DL/DT, IC, number of seeds, number of parthenocarpic segments, collected pulp yield, total soluble solids, total titratable acidity, ratio and Ph, in a completely randomized design. The results indicated that there was a variation in the biometric parameters for the average mass of the fruits, the variations were from 212g to 363g, with changes also in the number of tongues, which is an important attribute in pulp production, ranging from 2.10 to 3.15 tongues for fruits in the harvests from December to February, respectively. Regarding the chemical attributes, there was a change only in the analysis of total soluble solids within the average of the mapped locations and in terms of pH values, within the harvest seasons. Based on this, it can be concluded that the analyzed fruits are said to be of good quality for bacuri extraction activities, the storage forms are suitable for the duration of the pulp quality analyzed here and it can be concluded that the value of bacuri is the main source of income for small farmers, however, these in turn do not manage bacuri and do not have knowledge about how to carry out extraction procedures and proper management. The collection of bacuri constitutes a strategy for the maintenance of family income, an important tool for the maintenance of families. The bacuri fruit was used in natura, sold to middlemen, but the generation of pulp is what guarantees the farmer greater income. There is a lack of cultural practices that seek to promote in the extractive system.